Analisis Academic Burnout pada Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan - Langgi, Novedi Risanti; Pratiwi, Ni Made Firayanti (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
Academic burnout is a significant issue affecting students from various universities around the world. Burnout is characterized by emotional exhaustion, cynicism, and a sense of dissatisfaction with personal achievements, which negatively impacts academic performance and well-being. This study aims to analyze the level of burnout among students from the Faculty of Teacher Training and Education. The sample for this research consists of 100 students majoring in education or those from the Faculty of Teacher Training and Education. The burnout questionnaire used in this study is the Maslach Burnout Inventory General Student (MBI-GS(S)), which includes three indicators of burnout: exhaustion, cynicism, and academic efficacy. The results of the study show: (1) in the exhaustion indicator, students experience fatigue due to continuous work performed several times a month, (2) in the cynicism indicator, students experience a desire to distance themselves from work several times a month, (3) in the academic efficacy indicator, students feel ineffective in the tasks they are working on once a week. These results indicate the level of academic burnout among students in the FKIP faculty.